2018
DOI: 10.1051/matecconf/201819202006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on the groundwater sustainability in the lower Chao Phraya basin, Thailand

Abstract: Abstract. This research investigates the impact of climate change on the hydraulic heads of Thailand's Lower Chao Phraya basin. The research also determines the sustainability of groundwater as the result from climate change. In the study, the climatic scenario (IPSL-CM5A-MR) of the Representative Concentration Pathways (RCP) between 2.6, 4.5 and 8.5 were considered, and the simulations were carried out using the three-dimensional groundwater flow model (i.e. MODFLOW-2000) predicting the groundwater behavior b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This model was selected, because the scenarios offered the minimum bias and root mean square error on annual precipitation [22]. RCP 2.6 and 8.5 represent the most severe climate changes, and RCP 4.5 was the most likely event [23]. Soil erosion and sediment yield, due to climate change, were then predicted using the USLE and SDR models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was selected, because the scenarios offered the minimum bias and root mean square error on annual precipitation [22]. RCP 2.6 and 8.5 represent the most severe climate changes, and RCP 4.5 was the most likely event [23]. Soil erosion and sediment yield, due to climate change, were then predicted using the USLE and SDR models.…”
Section: Methodsmentioning
confidence: 99%
“…Nguyen and Chen [7] showed that the Shihmen is to predict long-term soil erosion and predict sediment yield in the reservoir, due to climate change, to improve the declining capacity of the reservoir and water planning and management. A Global Climate Model (GCM), Institute Pierre Simon Laplace-Climate Model version 5A (IPSL-CM5A-MR) from Coupled Model Intercomparison Project-5 (CMIP5) and three scenarios, i.e., RCP 2.6, RCP 4.5, and RCP 8.5, in the LPP watershed, were used to predict future rainfall data via Sananmuang's method [21], from the correlation between rainfall and water surface in the central part of Thailand [22,23]. Field measurements and other methods were used to validate the USLE and SDR results.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogeology is Tertiary-Quaternary formation that the depositions are coastal and fluvial deposits [18,19]. The aquifers consists mainly of sands, gravels and clay lenses, that can be divided into eight confined aquifers -the Bangkok (BK), Phra Pradaeng (PD), Nakorn Luang (NL), Nonthaburi (NB), Sam Khok (SK), Phayathai (PT), Thonburi (TB), and Pak Nam (PN) aquifers [1,9].…”
Section: Study Areamentioning
confidence: 99%
“…The effect of drought on water resources has been studied by Wongsa and Rangsiwanichpong et al [7,8]. Tanachaichoksirikun et al [9] reported that groundwater affected climate change: especially, in Thailand's Lower Chao Phraya (LCP) basin, groundwater is still sustainable but shortage may be faced in some aquifers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation